Plot and Characters in The Eyes Have It by Ruskin Bond - Riyanti, Suci (LPPM Universitas Bina Sarana Informatika, 2024)
Short stories often encapsulate a focused narrative, usually revolving around a singular event or conflict, and delve into the interactions among characters in a compact yet powerful context. Their brevity allows them to be read in one sitting, which is advantageous for readers with limited time. The intent behind this research is to deeply examine the intrinsic elements that constitute the heart of the story. Intrinsic elements are those foundational aspects that form a literary work, granting it its identity as a piece of literature. In the context of short stories, these elements play a crucial role in shaping the narrative and influencing its overall significance. This study will primarily focus on the plot and character development. An insightful analysis of the plot and characters is vital as they are fundamental components that govern the narrative and its emotional resonance. The plot often revolves around the conflicts—whether internal or external—that the characters encounter. By dissecting how conflicts arise, develop, and resolve, readers can uncover the underlying themes that the author aims to communicate.